Expression and Regulation of the Endogenous Retrovirus 3 in Hodgkin’s Lymphoma Cells - Kewitz, Stefanie; Staege, Martin S. (Frontiers in Oncology, 2013)
Human endogenous retroviruses (ERV) are an integral part of our genome. Expression of ERV is usually switched off but reactivation of ERV has been observed in varying human diseases including cancer. Recently, reactivation of ERV associated promoters in Hodgkin’s lymphoma (HL) cells has been described. Despite relatively good prognosis, not all patients with HL can be cured with the established therapy and this therapy is associated with severe late side effects. Therefore, new targets are required for the development of future treatment strategies. Reactivated ERV might represent such target structures. Therefore, we asked which ERV loci are expressed in HL cells. Using DNA microarray analysis, we found no evidence for a general activation of ERV transcription in HL cells. In contrast, we observed down-regulation of ERV3, an ERV with potential tumor suppressor function, in HL cells in comparison to normal blood cells. Interestingly, ERV3 was also differentially expressed in published DNA microarray data from resting versus cycling B cells. Treatment of HL cells with the histone deacetylase inhibitor vorinostat strongly up-regulated ERV3 expression. In addition, we observed up-regulation in HL cells after treatment with hypoxia-mimetic cobalt(II) chloride. Like vorinostat, cobalt(II) chloride inhibited cell growth of HL cells. Our results suggest that cell cycle inhibition of HL cells is accompanied by up-regulation of ERV3.